Stories From the Dendritic Cell Guardhouse - Hoober, J. Kenneth; Eggink, Laura L.; Cote, Robert (Frontiers in Immunology, 2019)
Phagocytic cells [dendritic cells (DCs), macrophages, monocytes, neutrophils, and mast cells] utilize C-type (Ca2+-dependent) lectin-like (CLEC) receptors to identify and internalize pathogens or danger signals. As monitors of environmental imbalances, CLEC receptors are particularly important in the function of DCs. Activation of the immune system requires, in sequence, presentation of antigen to the T cell receptor (TCR) by DCs, interaction of co-stimulatory factors such as CD40/80/86 on DCs with CD40L and CD28 on T cells, and production of IL-12 and/or IFN-α/β to amplify T cell differentiation and expansion. Without this sequence of events within an inflammatory environment, or in a different order, antigen-specific T cells become unresponsive, are deleted or become regulatory T cells. Thus, the mode by which CLEC receptors on DCs are engaged can either elicit activation of T cells to achieve an immune response or induce tolerance. This minireview illustrates these aspects with Dectin-1, DEC205, the mannose receptor and CLEC10A as examples.